Dear old peonies-for gene banks and gardeners; microsatellite fingerprinting of herbaceous peonies in Fennoscandia - Tanhuanpaa, Pirjo; Juhanoja, Sirkka; Oskarsson, Linnea; Marstein, Mari; Hartikainen, Merja (2021)
The genetic diversity of 334 herbaceous peonies from Fennoscandia was analysed using 18 microsatellites (simple sequence repeats, SSRs). The samples included peonies mostly from Finnish home gardens (284) and nurseries (5) as well as from Norwegian (20) and Swedish (25) peony collections. The study focused on the following species and hybrids: Paeonia anomala L., P. x hybrida Pall., P. officinalis 'Nordic Paradox' (Marstein 2015), P. tenuifolia L., and P. x festiva Tausch. The 18 microsatellites amplified a total of 249 alleles and were used to calculate genetic distances between samples and to build a dendrogram. In the dendrogram, samples formed clear groups according to their species. The outcome from the genetic analysis was mainly confirmed by preliminary morphological observations of the Finnish home garden samples performed within the project and the previous morphological study of peonies in Norwegian clone archives. The results of the study will be used to create a Finnish genetic resources collection of the most diverse and vigorous peonies, and to update the Norwegian and Swedish collections.